ANALYSIS OF WATER QUALITY USING PHYSICO-CHEMICAL PARAMETERS OF CHULHARDOH LAKE IN TUMSAR TALUKA, BHANDARA DISTRICT, MAHARASHTRA, INDIA (International Journal of Food and Nutritional Sciences, 2022)
This paper present to study of the Physico-Chemical parameter of Chulhardoh Lake in Tumsar Taluka in Bhandara District Maharashtra. Monthly variation in Physico-Chemical Parameters. The Physical included Temperature, pH, Turbidity and Chemical Includes, Alkalinity, Hardness, Chloride, Phosphate. We Analyzed for Period of Pre Monsoon(April-May) Monsoon (July-August) Post Monson (Oct-Nov) in year 2022.All the Physico-Chemical Parameter for Pre Monsoon, and Post Monsoon, Season are with the maximum permissible limit. The result included the Lake is Non-Polluted and it can be used for Domestic and Irrigation Purpose